Revealing The Motifs, Properties, and Phylogeny of Lupeol Synthase Using Bioinformatics Approach - Ika Qurrotul Afifah; Esti Wahyu Widowati (Universitas Khairun, 2021)
Lupane-type triterpenoid saponins are potent plants’ secondary metabolites for drug development as they showed various activities such as anticancer, Sarcoplasmic Reticulum Ca2+-ATPase (SERCA) activator which is very important for neurons, and antileishmanial. The triterpenoid saponin backbone is produced by cyclization and rearrangement of the 2,3-oxidosqualene precursor by the oxidosqualene cyclase. The type of oxidosqualene cyclase involved determines the type of saponins so it is referred to as a key enzyme. Lupane-type saponins are produced by 2,3-oxidosqualene cyclization through the chair-chair-chair conformation and the formation of various cation intermediates. This study aimed to analyze lupeol synthase, the key enzyme which determines the conversion of 2,3-oxidosqualene into lupane-type saponins. This in silico project was done using bioinformatics programs including Multiple Em for Motif Elicitation (MEME), ProtParam, and Molecular Evolutionary Genetic Analysis (MEGA-X) for relationship analysis. The amino acid sequences analysis using the MEME program showed that lupeol synthase has QW, DCTAE, and CYCR conserved motifs in the oxidosqualene cyclase family even though some evolutions were also present. Analysis of chemical and physical parameters with ProtParam indicated that lupeol synthase had lower stability than lanosterol synthase from Saccharomyces cerevisiae. The phylogenetic tree showed that lupeol synthase was closely related to other plant oxidosqualene cyclases. The results of this study are expected to support the modification strategy determination to increase the production of lupane-type saponins using a biotechnological approach in the pharmaceutical industry.